Reshaping the Future of Nepal’s Economy - Pradhan, Anjeela (Economic Review of Nepal, 2019)
Nepal’s economy has not been of any great success and satisfactory. Nepal has encountered inherent development constraint, which includes poverty; widening income inequality; unemployment and underemployment; rise in leisure class; decrease in production and productivity, capital flight; extensive corruption; absence of rule of law and order; institutionalized crime, BOP deficit, environmental degradation etc. The failures in economy have been more than the achievements and the problems created have been more than the problems solved, so ordinary people are unable to get the fruit of development. In these years every one use to feel development works do not seem satisfactory related to rapid increase in the economic problem normally day by day plus especially after the pandemic. However, it does not mean Nepal’s economy is heading towards wrong direction and we should abandon the path of economy. But the pace of heading is slow. So, for the reshaping the economy the Government need to be more liberal as well as strict where production, income and employment can be increased and be more watchful in disciplining both private and public sector and use of PPPs model for improving its efficiency especially in agriculture sector.